Risk reduction and perceived collective efficacy and community support among female sex workers in Tamil Nadu and Maharashtra, India: the importance of context. (3rd July 2012) - Guha, Mohua; Baschieri, Angela; Bharat, Shalini; Bhatnagar, Tarun; Sane, Suvarna Sanjay; Godbole, Sheela V; S, Saravanamurthy P; Mainkar, Mandar Keshav; Williams, Joseph; Collumbien, Martine
Abstract : Background: Empowering sex workers to mobilise and influence the structural context that obstructs risk reduction efforts is now seen an essential component of successful HIV prevention programmes. However, success depends on local programme environments and history. Methods: The authors analysed data from the Integrated Behavioural and Biological Assessment Round I cross-sectional survey among female sex workers in Tamil Nadu and Maharashtra. The authors used propensity score matching to estimate the impact of participation in intervention activities on reduction of risk (consistent condom use) and vulnerability (perceived collective efficacy and community support). Results: Background levels of risk and vulnerability as well as intervention impact varied widely across the different settings. The effect size ATT of attending meetings/trainings on consistent condom use was as high as 21% in Tamil Nadu (outside of Chennai) where overall use was lowest at 51%. Overall, levels of perceived collective efficacy were low at the time of the survey; perceived community support was high in Tamil Nadu and especially in Chennai (93%) contrasting with 33% in Mumbai. Consistent with previous research, the context of Mumbai seems least conducive to vulnerability reduction, yet self-help groups had a significant impact on consistent condom use (ATT=10%) and were significantly associated with higher collective efficacy (ATT=31%). Conclusions: Significant risk reduction can be achieved by large-scale female sex worker interventions, but the impact depends on the history of programming, the complexity of the context in which sex work happens and pre-existing levels of support sex workers perceive from their peers.